(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Jeongshindae movement carried out by victims of the military section system during the Korean occupation (1910-1945), along with women activists in South Korea whose agenda was to seek justice. The method used is historical research consisting of heuristics, criticism, and historiography. The occurrence of dynamics in the response of the Japanese government rejects legal accountability. The movement forms a strong transnational advocacy network and involves an inter-government organization to increase pressure on Japan. The resolution from the US DPR and the agreement between South Korea and Japan was achieved. But in the end, the resolution was ignored by the Japanese government, and the agreement was carried out unilaterally so that the legal responsibility and the demands of survivors were not fulfilled. Thus the issue of Jeongshindae cannot be completed at this stage.